Is patriotism a sufficient justification for liberal democracies to coerce conscription? - Tan, Jared Yue Rong (Nanyang Technological University, 2020)
Liberal democracies are legitimate when the country is able to justify their coercive actions to reasonable free and equal citizens. Liberal democracies are stable when free and equal citizens find overlapping consensus via public reason to form a unified political conception – that of the liberal democracy. This paper argues that patriotism is necessary for a stable liberal democracy by providing that overlapping consensus. However, patriotism cannot be achieved by free and equal citizens, and coercion is necessary to inspire patriotism. This paper argues that inspiration of patriotism through the coercive act of universal conscription cannot be justified legitimately by countries. This leads free and equal citizens at a fork with two unsavoury consequences, either accept an a stable but illegitimate political conception (which is no longer a liberal democracy) or demand for legitimacy, but end up without a unified scheme of cooperation.